Dampak Pemberdayaan Perempuan dan Penggunaan Anggaran Desa terhadap Pembangunan Sumber Daya Manusia di Desa Tanjung Garbus I - Shaliza Yustifa; Simon Patar Rizki; Daniel Ebenezer Silaban (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Women’s empowerment is an important aspect of village development because it contributes to improving the quality of human resources and community welfare. The success of empowerment programs is closely related to the allocation and utilization of Village Funds as a source of financing for community development. This study aims to analyze the allocation of Village Funds, their impact on women’s empowerment, their contribution to human resource development, and the implementation of empowerment programs in Tanjung Garbus I Village. This research employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation involving village officials, women’s groups, and related stakeholders. The data were analyzed using the interactive model of data reduction, data presentation, and conclusion drawing. The findings indicate that Village Funds have been allocated in accordance with applicable regulations and have supported various women’s empowerment programs, including skills training, PKK activities, and community economic development. These programs have contributed to improving women’s knowledge, skills, self-confidence, and economic participation. However, the implementation still faces challenges, particularly limited budget allocation for women’s empowerment and the absence of sustainable post-training assistance. The study implies that optimizing Village Fund allocation and strengthening mentoring programs are necessary to enhance the sustainability and effectiveness of women’s empowerment and human resource development at the village level.